Effectiveness Test of Kenikir Leaf Extract (Cosmos Caudatus) Against Death of House Flies (Musca Domestica): Uji Efektivitas Ekstrak Daun Kenikir (Cosmos Caudatus) Terhadap Kematian Lalat Rumah (Musca Domestica) - Romadania, Debby Suci; Ardiansyah, Syahrul (Universitas Muhammadiyah Sidoarjo, 2020)
Diarrhea causes frequent (BAB) defecation more than 3 times in 1 day with the consistency of liquid feces as a result of food contaminated with flies. The existence of an extract test using Kenikir Leaves can reduce the population of house flies. The purpose of this study was to determine the effectiveness of Kenikir Leaf (Cosmos caudatus) extract against the death of house fly (Musca domestica) with different concentrations and achieve Lc50 killing power. Experimental research using post-test Only Group Design, by means of accidental sampling technique. Based on the technique of the spray method, they were grouped into six treatments, namely the control group (without treatment), P1 (10%), P2 (20%), P3 (30%), P4 (40%), and P5 (50%). The process is carried out for 72 hours. Of the five concentrations that Lc50 has obtained 48.067% results so that it can kill flies as much as 63%. The results showed that there was a statistically significant effect using One-Way ANNOVA (p>0.05) on Kenikir Leaf extract which was able to kill flies with the best concentrations of 40% and 50%, respectively.